Mapping the research landscape of meat replacers in Romania: A bibliometric analysis and a cross-cluster synergy model of emerging trends - Ruxandra Malina Petrescu-Mag; Ioan Valentin Petrescu-Mag; Dacinia Crina Petrescu; Camelia Ginsca; Ioana Pistea (Future Foods)
Meat replacers are gaining global relevance as sustainable solutions to reduce environmental impact, improve public health and address animal welfare concerns. In Romania, these developments are particularly important, given the country's dietary habits and the growing emphasis on sustainable food systems. Consequently, the first objective is to systematically map the scientific literature using the VOSviewer software by analyzing publications from the Web of Science Core Collection. This bibliometric analysis identifies four major thematic areas, providing a foundation for the second objective. Building on this mapping, the second objective is to illustrate the interconnectedness of key research areas. To this end, a Cross-Cluster Synergy Model (CCSM) was developed, which synthesized the relationships between thematic clusters. Findings show that while much of the research in Romania focuses on integrating alternative proteins into livestock feed, fully plant-based products and synthetic meat remain underexplored. There are also knowledge gaps regarding the long-term health impacts and consumer acceptance of meat substitutes. Further research is needed on consumer acceptance, long-term health effects and the scalability of meat substitutes to drive innovation and sustainable practices. By mapping relationships, the CCSM provides a comprehensive understanding of how different research domains interact to drive innovation in meat replacers field.